The Canary in the Coalmine; Bee Declines as an Indicator of Environmental Health. (September 2016) - Goulson, Dave; Nicholls, Elizabeth
Bee declines have received much attention of late, but there is considerable debate and confusion as to the extent, significance and causes of declines. In part, this reflects conflation of data for domestic honeybees, numbers of which are largely driven by economic factors, with those for wild bees, many of which have undergone marked range contractions but for the majority of which we have no good data on population size. There is no doubt that bees are subject to numerous pressures in the modern world. The abundance and diversity of flowers has declined along with availability of suitable nest sites, bees are chronically exposed to cocktails of agrochemicals, and they are simultaneously exposed to novel parasites and pathogens accidentally spread by humans. Climate change is likely to exacerbate these problems in the future, particularly for cool-climate specialists such as bumblebees. Stressors do not act in isolation; for example pesticide exposure can impair both detoxification mechanisms and immune responses, rendering bees more susceptible to parasites. It seems certain that chronic exposure to multiple, interacting stressors is driving honeybee colony losses and declines of wild pollinators. Bees have a high profile and so their travails attract attention, but these same stressors undoubtedly bear upon other wild organisms, many of which are not monitored and have few champions. Those wild insects for which we do have population data (notably butterflies and moths) are overwhelmingly also in decline. We argue that bee declines are indicators of pervasive and ongoing environmental damage that is likely to impact broadly on biodiversity and the ecosystem services it provides.